DIFFERENCES IN BLOOD SUGAR LEVELS BEFORE AND AFTER MORNING AND AFTERNOON WALK IN TYPE II DIABETES MELITUS PATIENTS AT BABAKANSARI PUSKESMAS - Sri Mulyati Rahayu; Eneng Yeti; Rizki Muliani (Research Collaboration Community (RCC), 2023)
Diabetes Mellitus (DM) is a non-communicable disease which causes an increase in blood sugar levels and is at risk of causing disease complications. Walking is done to increase the sensitivity of insulin receptors. Blood vessels in the afternoon are more vasodilated than in the morning due to the effects of circadian rhythms which affect hormone action. This study aims to determine the difference in the average value of blood sugar levels before and after walking in the morning and afternoon in patients with type II DM. The research design used was a preexperiment with a pretest-posttest two group design approach. The sample of 20 respondents who are divided into 2 groups, namely the morning group of 10 people and the afternoon group of 10 people, with purposive sampling. The results of this study showed that the amount of decrease in blood sugar levels in the morning group was 31.6 mg/dL and the amount of decrease in blood sugar levels in the afternoon group was 43.5 mg/dL. The results of statistical tests in the morning group obtained a value of p = 0.007 (p <0.05) and in the afternoon group obtained a value of p = 0.005 (p <0.05). The results showed that the afternoon group was more effective in reducing average blood glucose levels as a result of vasodilatation of blood vessels which is influenced by circadian rhythms compared to the morning group, so it can be concluded that there are differences in blood sugar levels before and after walking in the morning and in the afternoon in patients with type II DM. Therefore it is advisable to walk, especially in the afternoon which can lower blood sugar levels more for type II DM sufferers in an effort to control blood sugar levels.